The effects of open vs. specific goals on flow and clutch states in a cognitive task. (November 2017) - Schweickle, Matthew; Groves, Scott; Vella, Stewart A.; Swann, Christian
Abstract: Objectives: Recent qualitative evidence suggests that two optimal psychological states (flow and clutch) underlie excellent performance in sport. That research further suggests that the type of goal pursued influences which state is experienced. This study aimed to examine the effects of goal types (i.e., open, specific, and do-your-best goals) on flow and clutch states during performance in a cognitive task, which was developed and has been used in sport. Secondary aims were to investigate the effects of goal types on objective and subjective performance, confidence, and perceived challenge. Design: This study employed a repeated measure design (mixed model). Method: Participants ( N  = 95; M age  = 24.89, SD  = 9.27) were randomised to one of three goal conditions and asked to perform a Letter and Number Identification Task, which was repeated for six attempts. Results: Participants prescribed open or do-your-best goals experienced significantly higher levels of flow than those prescribed specific goals, who conversely experienced significantly higher levels of clutch states. Participants assigned specific goals performed significantly better than those prescribed open or do-your-best goals. Those assigned open or do-your-best-goals reported greater perceived performance, higher confidence, and feeling more optimally challenged. Conclusions: These findings provide experimental support for the role of goal types in determining flow and clutch states, and further understanding of the psychological effects of these goal types. Implications are discussed, and recommendations are made for future research into the role of goals in experiencing flow and clutch states in sport and exercise. Highlights: Open and do-your-best goals foster higher levels of flow than specific goals. Specific goals lead to higher levels of clutch experience than other goal types. Specific goals promote higher objective performance than other goal types.